Bank-lending standards, loan growth and the business cycle in the Euro area - Sylvia Kaufmann; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
We study the relationship between bank lending standards, loan growth and the business cycle in the euro area and the US within a vector error correciton model using Bayesian estimation methods. To deal with the short data series available for the euro area, we exploit information from the estimated US system to improve the estimation of the euro area system. We find that tighter bank lending standards are associated with lower loan growth as well as lower output growth in both areas. Differences in reactions appear in the strength and the persistence of responses.
Keywords: E40; E50; 330; Bank Lending Standards; Bayesian Cointegration Analysis